VIOLENT COMMUNICATION IN THE HEADLINES OF DAILY NEWSPAPERS ON THE SUBJECT OF TRAFFIC DURING 2020 IN THE REPUBLIC OF SERBIA - Perišić, Nikola (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
The paper deals with the elements of violent communication in the headlines of daily newspapers in Serbia when it comes to the topic of traffic. Recent media research in Serbia shows a trend of increasing aggressive communication in the media, which has far-reaching consequences for all elements of society. The time sample for which the analysis was performed is the entire year 2020, which was specific because for almost two months a state of emergency was introduced due to the corona virus. The aim of the work is to indicate how much and in what way the use of violent language is noticeable in the daily press, as well as that it is applied in sensitive topics such as the topic of traffic where, according to the standards of professional media ethics, there should be respect for the victims. the injured and their families. The method used for research is discourse analysis and comparative method. The analysis shows that violent communication dominates in the tabloid media, while it is almost absent in the serious press. Aggressive communication occurs when reporting negative events such as traffic accidents and traffic violations. Jargon language and hyperbole are most often used as a tool for violent communication. Indeed, it was noticed that the topic of traffic is more dominant in the tabloid media. Only the daily newspaper Večernje novosti pays equal attention to news from the black chronicle related to traffic, but also to service information that is important to readers.
Keywords: violent communication, daily newspapers, media discourse, tabloids, traffic